An Analysis of Learning Devices as a Basis for Development of Biotechnology Module with Research Results for Biology Students - Nurul Fauziah; Iffa Ichwani Putri (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2019)
The purpose of this study is to describe the initial investigation data obtained as a basis for the development of biotechnology modules containing research results that will be developed later. The development model used in this study is the Plomp model which has been carried out until the initial investigation data stage. The results revealed in the analysis of the curriculum and the Semester Learning Plan (RPS) there were ten topics in biotechnology learning. The results of interviews conducted with lecturers in biotechnology courses also revealed obstacles in the implementation of biotechnology lectures, one of which was the lack of student references to study biotechnology. Student problem questionnaire revealed that students do not yet have a biotechnology module with a percentage of 1.08%. Student needs questionnaire revealed that students strongly agree the need to develop biotechnology modules containing research results with a percentage of 100%. The conclusion of this study is the need to develop biotechnology modules containing research results for biology students to help the lecture process in the classroom. Tujuan penelitian ini adalah untuk mendeskripsikan data investigasi awal yang didapatkan sebagai dasar pengembangan modul bioteknologi bermuatan hasil riset yang akan dikembangkan nantinya. Model pengembangan yang digunakan dalam penelitian ini adalah model Plomp yang telah dilakukan sampai tahap data investigasi awal. Hasil penelitian mengungkapkan pada analisis kurikulum dan Rencana Pembelajaran Semester (RPS) terdapat 8 topik dalam pembelajaran bioteknologi. Hasil wawancara yang telah dilakukan terhadap dosen pengampu mata kuliah biotekologi juga mengungkapkan kendala yang terdapat pada pelaksanaan perkuliahan bioteknologi yang salah satunya kurangnya referensi mahasiswa untuk mempelajari bioteknologi. Angket permasalahan mahasiswa mengungkapkan mahasiswa belum memiliki modul bioteknologi dengan presentase 1,08%. Angket kebutuhan mahasiswa mengungkapkan mahasiswa sangat setuju perlu dikembangkannya modul bioteknologi bermuatan hasil riset dengan presentase 100%. Kesimpulan penelitian ini adalah perlu dikembangkannya modul bioteknologi bermuatan hasil riset untuk mahasiswa biologi untuk membantu proses perkuliahan di kelas. Kata kunci: hasil riset, modul bioteknologi, studi pendahuluan